Pediatric dentistry procedures performed within the Brazilian National Health System in the state of Rio Grande do Sul before and during the COVID-19 pandemic: difference between the years 2018 and 2021 - Hellen Monique da Motta; Lara Emmile Evangelista Valença; Luiza Helena de Souza Fernandes; Rafaela Corrêa Martins; Letícia Regina Morello Sartori; Sarah Arangurem Karam (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to analyze the difference in the number of primary teeth dental procedures performed within the Brazilian National Health System (SUS) in the state of Rio Grande do Sul, before and during the COVID-19 pandemic. Methods: this was a descriptive ecological study, using secondary data from the SUS Outpatient Information System (SIA-SUS), from 2018 to 2021, in the state and in its seven health macro-regions; we calculated the relative and absolute frequencies and the percentage difference of the dental procedures performed. Results: 94,443 and 36,151 dental procedures were recorded before and during the pandemic, respectively, corresponding to a 61.7% reduction; relevant percentage reductions were found in restorative procedures, which reached 20% in the southern region of the state; an increase in the percentage of exodontic and endodontic procedures was found. Conclusion: the results suggest that the COVID-19 pandemic had negative repercussions on the performance of primary teeth dental procedures in Ro Grande do Sul.